2023
DOI: 10.1111/bjh.19037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of chimeric antigen receptor T‐cell therapy for mantle cell lymphoma with secondary central nervous system involvement

Abstract: SummaryData describing outcomes of chimeric antigen receptor (CAR) T‐cell therapy in patients with secondary central nervous system (SCNS) involvement of mantle cell lymphoma (MCL) are limited. We identified 10 patients with MCL and SCNS involvement treated with anti‐CD19 CAR T‐cell therapy at three US academic centres. Frequent objective responses were observed in the CNS (86%) and systemically (90%), and the 1‐year progression‐free survival was 47%. Seven patients developed immune‐effector‐cell‐associated‐ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In our cohort, the ORR was 100%, with 92% achieving a CR at the 1-month interval. The US Lymphoma CAR-T Consortium study did not report SCNS specific outcomes, but Ryan et al 10 reported a 12-month PFS of 36% and OS of 71% in patients with active CNS disease, which was slightly higher than that reported in our case series (25% and 63%, respectively). As far as adverse events of CRS and ICANS are concerned, we had no patients with grade ≥3 CRS, consistent with the data from the US Lymphoma CAR-T Consortium study and Ryan et al.…”
contrasting
confidence: 84%
See 2 more Smart Citations
“…In our cohort, the ORR was 100%, with 92% achieving a CR at the 1-month interval. The US Lymphoma CAR-T Consortium study did not report SCNS specific outcomes, but Ryan et al 10 reported a 12-month PFS of 36% and OS of 71% in patients with active CNS disease, which was slightly higher than that reported in our case series (25% and 63%, respectively). As far as adverse events of CRS and ICANS are concerned, we had no patients with grade ≥3 CRS, consistent with the data from the US Lymphoma CAR-T Consortium study and Ryan et al.…”
contrasting
confidence: 84%
“…Our results are in line with the 2 prior studies with respect to ORRs and CR rates. 9 , 10 , 11 The US Lymphoma CAR-T Consortium study included 16 patients with SCNS involvement and reported an ORR of 81%, with CR rates of 75% in patients with active CNS disease. 9 Ryan et al 10 reported an ORR of 86% in patients with active CNS disease (n = 7) with CR rates of 28.6%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They were heavily pretreated and 8/10 had received prior CNS-directed therapies and prior cBTKi exposure was common. 10 The ORR in patients with CNS disease at time of infusion (n = 7) was 86% (CR 28.6%), with median PFS of 11.7 months and median OS not reached after median follow-up of 15.4 months. One patient experienced grade (G)3 CRS, and there were no G4-G5 events.…”
mentioning
confidence: 92%
“…9 Wang et al describe outcomes for 16 patients with CNS MCL treated with brexu-cel, in which efficacy was comparable to those without CNS involvement (n = 152) (ORR 81% vs. 91%, CR 75% vs. 83%, respectively; median progression-free survival [PFS] 9 months vs. 17 months). 9 The present study 10 describes the detailed clinical course for 10 patients treated with anti-CD19-directed autologous CAR-T-cell therapy at three US academic centres; 9 with brexu-cel and 1 with axi-cel. They were heavily pretreated and 8/10 had received prior CNS-directed therapies and prior cBTKi exposure was common.…”
mentioning
confidence: 99%